2013
DOI: 10.4100/jhse.2013.83.02
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of ground reaction force during different angle of squatting

Abstract: Dali, S., Justine, M., Ahmad, H. & Othman, Z. (2013). Comparison of ground reaction force during different angle of squatting. J. Hum. Sport Exerc., 8(3), pp.778-787. Squatting is a form of closed kinetic chain movement which commonly being employed in exercise training. However, little is known regarding the amount of force being imposed on the knee at different angles of squat. Thus, the purpose of this study was to compare the vertical ground reaction force (VGRF) at different angles of squatting among the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Contextualizing this matter into the working environment, it can be observed that within tasks involving loads movement with squat, a direct relationship between the act of squatting and the occurrence of those pathologies is evidenced (Dali, Justine, Ahmad, & Othman, 2013;Lee et al, 2016;Sadler, Graham, & Stevenson, 2013). They affect more females than males in a proportion of two women for each man, with a prevalence of approximately 11-14% on physically inactive population and of 25-40% on those performing any physical activity (Van Middelkoop, Van Linschoten, Berger, Koes, & Bierma-Zeinstra, 2008;Wood, Muller, & Peat, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Contextualizing this matter into the working environment, it can be observed that within tasks involving loads movement with squat, a direct relationship between the act of squatting and the occurrence of those pathologies is evidenced (Dali, Justine, Ahmad, & Othman, 2013;Lee et al, 2016;Sadler, Graham, & Stevenson, 2013). They affect more females than males in a proportion of two women for each man, with a prevalence of approximately 11-14% on physically inactive population and of 25-40% on those performing any physical activity (Van Middelkoop, Van Linschoten, Berger, Koes, & Bierma-Zeinstra, 2008;Wood, Muller, & Peat, 2011).…”
Section: Introductionmentioning
confidence: 99%